The Effects of Flipped Learning on Learning and Motivation of Upper Secondary School Physical Education Students - Ferriz-Valero, Alberto; Østerlie, Ove; Penichet-Tomas, Alfonso; Baena-Morales, Salvador (Frontiers in Education, 2022)
New technologies are increasingly linked to the educational world. It is necessary to develop pedagogical approaches such as flipped learning so that education and technology improve the quality of teaching. Over the years this pedagogical approach has developed quite a bit; however, the scientific literature in physical education is still limited. The objective of the present study was to quantitatively evaluate the effects of the application of flipped learning in the acquisition of the conceptual contents of sport, in the case of the present study through volleyball. A total of 265 upper secondary school students participated in the study (126 boys: 47.9% and 137 girls: 52.1%). The total sample set was divided into two treatment groups. The first experimental treatment group received lessons with the support of flipped learning, through the Edpuzzle platform. The second treatment group or control group received the same content as the first group through traditional methodology. The findings showed that upper secondary students benefited from flipped learning in their cognitive learning about volleyball in physical education, compared to the control group. Further, the findings showed the same results on motivation, although certain differences appeared according to sex, where boys seemed to develop autonomous motivation more than girls.